In vitro evaluation of anti-dengue activity of selected synthetic schiff bases and traditional chinese medicinal plants extracts - Maqsood, Maryam (2018)
During the last few decades, dengue virus (DENV) has emerged as the major virus spread by mosquito that can cause life threatening disease. Recently, it has spread to more than a hundred countries around the globe and still lacks a specific treatable medication. Hospitals provide only supportive and symptomatic treatment hence the development of a safe and effective antiviral is an urgent need. To identify new antivirals against DENV, realms of both synthetic compounds and ethnomedicine were explored.